Learn Python by building data science applications : a fun, project-based guide to learning Python 3 while building real-world apps - Kats, Philipp; Katz, David (Packt Publishing Ltd., 2019)
This book will teach Python to complete beginners through a set of 3 practical projects. Its content goes over developing a handful of scripts, performing data analysis, train machine learning models and roll them into production. We will further outline the advanced topics and direct readers to relevant resources.